2021
DOI: 10.1177/00953997211055102
|View full text |Cite
|
Sign up to set email alerts
|

The Iterative Process of Legitimacy-Building in Hybrid Organizations

Abstract: Hybrid organizations face the fundamental challenge of building legitimacy. To deal with this challenge in administrative theory and practice, we apply an analytical framework following an organizational logic of legitimacy building to an exemplary case of hybridity—the Swiss Institute for Translational and Entrepreneurial Medicine. Our framework application illustrates that pragmatic legitimacy (i.e., establishing instrumental value) must be built before moral legitimacy (i.e., fostering normative evaluation)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…These findings are in line with Huybrechts and Nicholls (2013) who noticed that new collaborative relationships between social enterprises and other businesses require both pragmatic and moral legitimacy. The results of the study further confirm the idea of the development of legitimacy in hybrid organisations, like CBSEs, as a temporal process in which “pragmatic legitimacy has to be secured before moral and cognitive legitimacy can be achieved” (Rosser et al. , 2022, p. 1136).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…These findings are in line with Huybrechts and Nicholls (2013) who noticed that new collaborative relationships between social enterprises and other businesses require both pragmatic and moral legitimacy. The results of the study further confirm the idea of the development of legitimacy in hybrid organisations, like CBSEs, as a temporal process in which “pragmatic legitimacy has to be secured before moral and cognitive legitimacy can be achieved” (Rosser et al. , 2022, p. 1136).…”
Section: Discussionsupporting
confidence: 71%
“…As important as the legitimacy of service production is, the social acceptability of rural communities as service providers alongside and in cooperation with the public sector has rarely been examined in public administration literature (Kleinhans, 2017;Rosser et al, 2022;Vestrum et al, 2017). As previous research has demonstrated, different social groups can evaluate and judge an organisation, its activities and essence, very differently (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staessens et al (2019) observe a direct relationship between stronger economic and social performance indicating that financially viable operations contribute to greater legitimacy. As legitimacy is not static, but rather constantly renegotiated (Suddaby et al, 2017), it is important to create mechanisms for the resources accrued through pragmatic and moral legitimacy to be put to work to move the organisation to higher levels of legitimacy (cognitive) (Rosser et al, 2021). 'Re-investing' moral legitimacy gains into pragmatic legitimacy gains and vice versa would create a recursive feedback effect reinforcing the two types of legitimacy.…”
Section: Discussion: a Pragmatic And Moral Legitimacy Recursive Processmentioning
confidence: 99%
“…Successful outcomes are difficult to articulate for hybrid organisations due to the combination of distinct institutional logics (e.g. profit and non‐profit) (Battilana & Lee, 2014; Rosser et al., 2021) and the hybrid identity of their leaders (e.g. manager vs. health practitioner) (Martin et al., 2021; Numerato et al., 2012).…”
Section: Introductionmentioning
confidence: 99%